Utilization of clinical pathway on open appendectomy: A quality improvement initiative in a private hospital in the Philippines - Hilario, Allan L.; Oruga, Jonathan David H.; Turqueza, Maria Presentacion P.; Hilario, Donnatella V. (International Journal of Health Sciences, 2018)
Objective: This study was done to evaluate the utilization of Clinical Pathway (CP) on open appendectomy as a quality improvement (QI) initiative. Methods: The CP document was developed from the clinical practice guideline created by the Philippine College of Surgeons using an event-timeline tabular checklist format. After a hospital-wide education, the CP was implemented on January 1, 2010 as the QI intervention. Appendectomies done four years prior to the intervention were assigned to the pre-pathway group while those done five years after were assigned to the post-pathway group. Demographic data were collected including the different clinical outcomes such as the average length of stay, co-morbidity, diagnostic modality used, hospital cost, and variance rate. Data were presented as mean ± SD and percentage which ever were applicable. Statistical analysis was done using Student t-Test for numerical data and chi-square for dichotomous data. Significance was set at p<0.05. Results: Two hundred ninety five patients were included in the study. Separate analysis was done for uncomplicated (Pre-pathway Group, n=49 and Post-pathway group, n=139) and complicated (Pre-pathway Group, n=38 and Post-pathway Group, n=69) open appendectomies. Results showed that diagnosis was achieved through history and physical examination. Ultrasound use did not significantly differ between groups and types of open appendectomy. Major findings showed significant decrease in ALOS, hospitalization cost, and variance in the post-pathway group compared with the pre-pathway group (p<0.05). Conclusion: These findings supported the use of CP in QI of healthcare in commonly done surgeries like appendectomy.